2010
DOI: 10.1007/s11434-010-3269-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross wavelet analysis of the relationship between total solar irradiance and sunspot number

Abstract: Using the observational data of total solar irradiance (TSI) from 1976 to 2006, the evolution of total solar irradiance and the relationship between TSI and sunspot number (SSN) have been analyzed with the wavelet technique. The results of the continuous wavelet transform (CWT) indicate that the TSI has multi-scale evolutionary characteristics. In the low frequency band, the TSI and SSN show similar variation with a significant and steady oscillation period from 8 to 11.4 a. While in the high frequency band, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…SSN affects on Total Solar Irradiance (TSI) seems to call out sun from the causes of climate change (e.g. [48]) even if the complexity of the Sun-Earth system make conclusions still hard to be done (e.g. [13]).…”
Section: Data Sourcementioning
confidence: 99%
“…SSN affects on Total Solar Irradiance (TSI) seems to call out sun from the causes of climate change (e.g. [48]) even if the complexity of the Sun-Earth system make conclusions still hard to be done (e.g. [13]).…”
Section: Data Sourcementioning
confidence: 99%
“…众多研究表明, 太阳活动具有周期性变 化规律 [5,6] ; 其中以太阳黑子约11 a的周期 [7,8] 和太阳 磁场极性约22 a的周期性 [9] 变化最为显著. 赵明宇等 人 [10] 、杨若文等人 [11] 对太阳黑子与太阳活动之间的 关系进行了深入的研究, Haigh [12] , Friis-Christensen和 Lassen [13] 、赵新华和冯学尚 [14] 、刘立波等人 [15] 、赵 平等人 [16] 在太阳活动对全球气候及地表环境的影响 取得了可喜的成果; 太阳活动的周期性变化导致了 地球表层环境和全球气候也具有类似的周期性变化 规律 [17] . 多年来关于太阳活动的周期性韵律产生的 机制 [18,19] 逐渐产生多种不同的形成理论, 其中以太 阳质心绕太阳系质心的周期性运动与太阳活动具有 一定的同步性成为当前学者关注的焦点 [20~23] .…”
Section: 也试图在行星运动对太阳活动产生的影响方面做出unclassified
“…Yang and Yang (2013) and Li et al (2010) used this index and found an 11-year period for the sunspot and a 22-year period for the magnetic solar activity (Qu, 2007). Yang et al (2010) and conducted much research on the sunspot cycle. Friis-Christensen and Lassen (1991), Haigh (1996), Sharp (2013), Mörner (2010), Zhao and Feng (2014), Liu et al (2011), and Zhao et al (2011) successfully investigated the changes in surface environment and global climate on the basis of solar activity.…”
Section: Introductionmentioning
confidence: 99%